Between Covering the Basic Needs and Self-fulfilment Jobs - Why We Need a Better EU Strategy for Employment - Ana-Maria Coatu (Agora International Journal of Economical Sciences (AIJES), 2022)
This article tries to present two distinct concepts in relation to labour: basic-needs jobs and self-fulfilment jobs. Those two concepts should be taken into account when designing and envisioning EU work strategies.
Keywords: 330